Metformin-Induced MicroRNA-34a-3p Downregulation Alleviates Senescence in Human Dental Pulp Stem Cells by Targeting CAB39 through the AMPK/mTOR Signaling Pathway - Shuo Zhang; Rong Zhang; Pengyan Qiao; Xiaocao Ma; Rongjian Lu; Feifan Wang; Chuanjie Li; Lingling E; Hongchen Liu (Hindawi Limited, 2021)
Dental pulp stem cells (DPSCs) are ideal seed cells for the regeneration of dental tissues. However, DPSC senescence restricts its clinical applications. Metformin (Met), a common prescription drug for type 2 diabetes, is thought to influence the aging process. This study is aimed at determining the effects of metformin on DPSC senescence. Young and aging DPSCs were isolated from freshly extracted human teeth. Flow cytometry confirmed that DPSCs expressed characteristic surface antigen markers of mesenchymal stem cells (MSCs). Cell Counting Kit-8 (CCK-8) assay showed that a concentration of 100 μM metformin produced the highest increase in the proliferation of DPSCs. Metformin inhibited senescence in DPSCs as evidenced by senescence-associated β-galactosidase (SA-β-gal) staining and the expression levels of senescence-associated proteins. Additionally, metformin significantly suppressed microRNA-34a-3p (miR-34a-3p) expression, elevated calcium-binding protein 39 (CAB39) expression, and activated the AMP-activated protein kinase (AMPK)/mammalian target of rapamycin (mTOR) signaling pathway. Dual-luciferase reporter assay confirmed that CAB39 is a direct target for miR-34a-3p. Furthermore, transfection of miR-34a-3p mimics promoted the senescence of DPSCs, while metformin treatment or Lenti-CAB39 transfection inhibited cellular senescence. In conclusion, these results indicated that metformin could alleviate the senescence of DPSCs by downregulating miR-34a-3p and upregulating CAB39 through the AMPK/mTOR signaling pathway. This study elucidates on the inhibitory effect of metformin on DPSC senescence and its potential as a therapeutic target for senescence treatment.